Which specific angle measurement criteria should be used to define forward head and rounded shoulder posture: an evidence-based commentary - Sandrey, M. A. (International Journal of Athletic Therapy & Training, 2021)
Abstract: Postural distortions in the upper limb are prevalent and change the anatomical alignment, which alters force couples and the biomechanics of the body. Forward head posture (FHP) and rounded shoulder posture (RSP) are the two that are most prevalent. Measurement techniques using the craniovertebral angle for FHP and forward shoulder angle for RSP have been used both clinically and in the literature. However, what is not known is what specific criteria can be consistently used to define FHP and RSP as reference angles lack vigorous validity and there is a shortage of quantity, quality, and consistency of the evidence. Thus, there is much to be learned about postural classifications and the effect on the kinetic chain, supporting the need for further research in this area. As it is important to classify those who may need exercise and therapeutic intervention, following evidence-informed practice to inform decision-making clinicians should continue to evaluate posture, as well as examine scapular kinematics and muscle activity and the effects of interventions to improve posture. Therefore, determining whether FHP and RSP are present is paramount for the treatment to be successful.